ANALISIS PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET, DAN CURRENT RATIO (Studi pada Industri Manufaktur di Bursa Efek Indonesia Periode Tahun 2010-2012) - Yasin, Achmad Agus; Chabachib, M.; Haryanto, Mulyo (JURNAL BISNIS STRATEGI, 2013)
This research  was held to test the influence of DER, profitability,  and liquidity  toward  DPR to increase  company  value. The problems  in this research gap from the former  research and the fenomena bussiness gap from the manufacturing company data over period 2010-2012 in the Indonesian  Capital  Market  Directory.  Therefore a deeper  research  to obrserve the problems  which  influent DPR and company  value with reasonable theory is needed.  The factors consist of DER, profitability,  and liquidity  variables.Sampling technique used is purposive sampling with criteria  as manufacturing  industry in IDX who provide financial report and traded during period 2009 through 2012 and forwarded to ICMD.  The Data is based on publicity Indonesia Market Directory since 2009 to 2012. Obtained by amount sampel as much 15 company from 185 manufacturing industry in IDX2009-2012  period. Analysis technique used is doubled regression with smallest squareequation and hypothesis  test use t-statistic to test coefficient of regression  partial and also f-statistic to test the truth of collectively influence in level of significance  5%. Others also done a classic  assumption  test covering normality test, multicolinierity test, and heteroscedastisity  test.During research period  show  as data research was normally distributed.  Based on multicolinierity test, and heteroscedasticity  test variable digressing  of classic assumption has not founded, its indicate that the available data has fulfill the condition to use multi linier regression model. From the result of analyse indicate  that ROA  in partial significant toward  DPR and  DER, DPR and  ROA in partial significant  toward company value